Pengaruh Strategi Promosi KPR Syariah terhadap Tingkat Kesadaran dan Minat Masyarakat dalam Memiliki Rumah (studi kasus BTN Syariah Cabang Bogor) - solihah, siti alis; Hakiem, Hilman; Kosim, Ahmad Mulyadi (IAIN Tulungagung, 2018)
Based on the results of national records of sharia mortgage finance is still less exist than the conventional bank mortgage system. Some of the factors that trigger such problems include the lack of public awareness of the values ââof sharia that the activities of usury in conventional banking practices is haram, the lack of public knowledge about the difference between the system and the principles of conventional banks and Islamic, public opinion that kpr with syariah system is more expensive than conventional kpr, without knowing the advantages of kpr syariah system. Therefore it is necessary for the delivery of information and education from Islamic banking that can be done through a promotional strategy. Based on the above reasons, this study aims to find out how the influence of promotional strategies on the publics perspective regarding the product kpr in Islamic banking, as well as the effect on the interest of the community in choosing the product of sharia kpr by using murabahah scheme. The type of research used is quantitative research with simple regression model through mediation variables. Mediation variable analysis technique using Causal Step (Baron and Kenny) and Product of Coefficient (Sobel Test) method. The result of this research is promotion strategy influence to interest with value a â 0 at 95% confidence level. The level of public awareness significantly affects interest with the value of b = 0.774 at sig = 0,000. Public awareness mediate partially influence of promotion strategy to interest with marked decrease of c value, that is from c = 0,534 become c = 0,222 or c> c and result of calculation of z value count get value 1,686 bigger than z table (df = N- 2) with a significance level of 0.05 that is equal to 0.999